Twelve-Month Outcomes of Community-Based Differentiated Models of Multimonth Dispensing of ART Among Stable HIV-Infected Adults in Lesotho: A Cluster-Randomized Noninferiority Trial. (1st November 2020) - Tukei, Betty B.; Fatti, Geoffrey; Tiam, Appolinaire; Ngorima-Mabhena, Nicoletta; Tukei, Vincent J.; Tshabalala, Itumeleng; Sejana, Veronica M.; Muzenda, Trish; Mokoroane, Lincoln M.; Sehlabo, Lebelang; Maotoe, Thapelo; Mirembe, Justine K.; et al.
Abstract : Background: Lesotho adopted the test-and-treat approach for HIV treatment in June 2016, which increased antiretroviral treatment (ART) clinic volume. We evaluated community-based vs. facility-based differentiated models of multimonth dispensing of ART among stable HIV-infected adults in Lesotho. Methods: Thirty facilities were randomized to 3 arms, facility 3-monthly ART (3MF) (control), community ART groups (3MC), and 6-monthly community distribution points (6MCD). We estimated risk differences (RDs) between arms using population-averaged generalized estimating equations, controlling for baseline imbalances and specifying for clustering. The primary outcome was retention in ART care by intention-to-treat and virologic suppression as a secondary outcome (ClinicalTrials.gov: NCT03438370). Results: A total of 5, 336 participants were enrolled, with 1898, 1558, and 1880 in 3MF, 3MC, and 6MCD, respectively. Retention in ART care was not different across arms and achieved the prespecified noninferiority limit (−3.25%) between 3MC vs. 3MF (control); 6MCD vs. 3MF; and 6MCD vs. 3MC, adjusted RD = −0.1% [95% confidence interval (CI): −1.6% to 1.5%], adjusted RD = −1.3% (95% CI: −3.0% to 0.5%), and adjusted RD = −1.2% (95% CI: −2.9% to 0.5%), respectively. After 12 months, 98.6% (n = 1503), 98.1% (n = 1126), and 98.3% (n = 1285) were virally load (VL) suppressed in 3MF, 3MC, and 6MCD, respectively. There were no differences in VL between 3MC vs. control and 6MCD vs. control, risk ratio (RR) = 1.00 (95% CI: 0.98 to 1.01) and RR = 1.00 (95% CI: 0.98 to 1.01), respectively. Conclusions: There were no differences in retention and VL suppression for stable HIV-infected participants receiving multimonth dispensing of ART within community-based differentiated models when compared with the facility-based standard-of-care model.